A systematic review of the causes of failure of Revision Total Hip Arthroplasty - Kenney, Connor (J Orthop, 2019)
This study reviewed literature published in the last 10 years to investigate the reasons for revision failure. A total of 9952 revisions were identified and it was determined that the number one cause of failure was aseptic loosening (23.19%), followed by instability (22.43%) and infection (22.13%). Further analysis of applicable revisions investigated BMI and age at the failure rates. The rate of rerevision in obese patients was markedly higher (p < 0.01) compared to non-obese patients and individuals receiving a revision THA under the age of 55 are at a higher risk of rerevision (p < 0.01).